Yearning, learning and conceding: (Some of) the reasons people change their childbearing intentions - Maria Iacovou; Lara Patrício Tavares (University of Essex, Institute for Social and Economic Research (ISER), 2010)
People's childbearing intentions change over the course of their reproductive lives. These changes have been conceptualised as occurring in response to the realisation that an individual is unlikely to achieve his or her intended fertility, because of constraints such as the biological clock or lack of a partner. In this paper we find that changes to childbearing plans are actually influenced by a much wider range of factors than this. People change their plans in response to the wishes of their partners, in response to social norms, as the result of re-partnering, and as the result of learning about the costs and benefits of parenthood; there are also differences between the factors which influence men's and women's decision-making. A key feature of this paper is that, in a departure from existing studies in this area, we use a flexible analytical framework which enables us to analyse increases in planned fertility separately from decreases. This allows us to uncover several complexities of the decision-making process which would otherwise be hidden, and leads us to conclude that the determinants of increases in planned fertility are not simply equal and opposite to the determinants of decreases.
Keywords: J12; J13; 330; fertility intentions; individual decision-making; constraints to childbearing; intention-behaviour mismatch; Familienplanung; Geburtenrate; Verhalten; Persönlichkeitspsychologie; Lebensverlauf; Großbritannien